Cu2+ cation-exchange in ZnxCd1-xS thin films for neuromorphic devices - Boratto, Miguel H. [UNESP]; Linhares, Alexandro A.; Congiu, Mirko [UNESP]; Batagin-Neto, Augusto [UNESP]; Pla-Cid, Cristiani C.; Pasa, André A.; Graeff, Carlos F.O. [UNESP] (Elsevier, 2021)
Neuromorphic devices are promising for more efficient informatics systems, containing electronic analog circuits capable of simulating brain synaptic cells to mimic neuro-biological architectures present in the nervous system. Such devices may be employed in a microfluidic system with materials with cationic exchange (CE) mechanisms, to control the conductivity states and allow multilevel switching capabilities. Thus, CE of Cu2+ in ZnxCd1-xS (0 ≤ x ≤ 1) thin films is hereby reported. The CE dynamics are studied as a function of the different Zn and Cd content in the film. Cu2+ ions, provided by a Cu(NO3)2 solution, can replace Zn2+ and Cd2+ ions into the insulating ZnxCd1-xS films, increasing their electrical conductivity. Reversible CE is achieved with the aid of Zn or Cd diethyldithiocarbamate (DTC) solutions. This CE mechanism provides several different conduction states in the film, which are proportional to the dipping time in both Cu(NO3)2 and Zn/Cd-DTC solutions. Electrical and compositional analysis by XPS and EDS are thoroughly investigated to comprehend the cation exchange process. Samples with higher Cd concentration present more efficient CE processes with Cu2+. These results are supported by a comprehensive discussion considering both thermodynamics solubility products, Gibbs free energy of formation, and chemical softness of the elements involved in the reaction, essential to understanding the driving force of the CE processes.
Keywords: Cation exchange; Multiple conduction states; Neuromorphic devices; Sulphide; ZnCdS